Salmonella flagella confer anti-tumor immunological effect via activating Flagellin/TLR5 signalling within tumor microenvironment - Jianxiang Chen; Yiting Qiao; Guo Chen; Cunjie Chang; Heng Dong; Bo Tang; Xiawei Cheng; Xiufeng Liu; Zichun Hua (Elsevier, 2021)
Salmonella: mediated cancer therapy has achieved remarkable anti-tumor effects in experimental animal models, but the detailed mechanism remains unsolved. In this report, the active involvement of the host immune response in this process was confirmed by comparing the tumor-suppressive effects of Salmonella in immunocompetent and immunodeficient mice bearing melanoma allografts. Since flagella are key inducers of the host immune response during bacterial infection, flagella were genetically disrupted to analyse their involvement in Salmonella-mediated cancer therapy. The results showed that flagellum-deficient strains failed to induce significant anti-tumor effects, even when more bacteria were administered to offset the difference in invasion efficiency. Flagella mainly activate immune cells via Flagellin/Toll-like receptor 5 (TLR5) signalling pathway. Indeed, we showed that exogenous activation of TLR5 signalling by recombinant Flagellin and exogenous expression of TLR5 both enhanced the therapeutic efficacy of flagellum-deficient Salmonella against melanoma. Our study highlighted the therapeutic value of the interaction between Salmonella and the host immune response through Flagellin/TLR5 signalling pathway during Salmonella-mediated cancer therapy, thereby suggesting the potential application of TLR5 agonists in the cancer immune therapy.